Cause-and-Effect relationship between FGFR1 expression and epithelial-mesenchymal transition in EGFR-mutated non-small cell lung cancer cells. (June 2019) - Vad-Nielsen, Johan; Gammelgaard, Kristine Raaby; Daugaard, Tina Fuglsang; Nielsen, Anders Lade
Highlights: Retrospective analyses reveals FGFR1 expression and EMT correlation across NSCLC cells. EMT drives increased FGFR1 expression in EGFR -mutated NSCLC cells. Increased FGFR1 expression is insufficient to drive concomitant EMT in EGFR -mutated NSCLC cells. Abstract: Objectives: Increased FGFR1 expression is associated with resistance to tyrosine kinase inhibitors (TKIs) in EGFR -mutated NSCLC cells and often concomitant with epithelial to mesenchymal transition (EMT). However, the cause-and-effect relationship between increased FGFR1 expression and EMT in the genetic background of EGFR -mutated non-small cell lung cancer (NSCLC) cells is not clear. Previous studies have specifically addressed the relationship between EMT and increased FGFR1 expression in the context of simultaneous TKI-mediated blocking of EGFR-signaling. Here, in the context of EGFR -mutated NSCLC cells with active EGFR-signaling, we have examined whether increased FGFR1 expression drives EMT or is an EMT passenger event. Materials and methods: For cause-and-effect analyses between EMT and FGFR1 expression, including expression of alternative spliced FGFR1 isoforms, we used CRISPR-dCAS9-SAM-mediated induction of the endogenous FGFR1 and ZEB1 genes, as well as biochemical EMT-induction, in PC9 and HCC827 NSCLC cell lines harboring activating EGFR -mutations. Results: We find that FGFR1 expression correlates with a ZEB1 -associated EMT gene expression profile in NSCLC cells. In experiments using NSCLC cell lines harboring activating EGFR -mutations we show that CRISPR-dCAS9-SAM-mediated induction of FGFR1 expression is neither driving an increase in ZEB1 expression nor EMT characteristics. However, CRISPR-dCAS9-SAM-mediated induction of ZEB1 expression drives EMT characteristics and an increase in FGFR1 expression. Biochemical induction of EMT also drives an increase in FGFR1 expression. Conclusion: From our findings concerning the cause-and-effect relationship in the genetic background of EGFR -mutated NSCLC cells, we conclude that an increase in ZEB1 expression is a driver of EMT resulting in concomitant increased FGFR1 expression, whereas an increase in FGFR1 expression is insufficient to drive concomitant EMT.